Formulation Herbal Mouthwash Combination Extract of Ginger and Lemongrass as Antibacterial Causes of Halitosis in Diabetes Mellitus Patients - Masriadi; Sukmawati; Hasta Handayani Idrus (Institute of Medico-legal Publications Pvt Ltd, 2021)
Background. Ginger and lemongrass are plants known as the king of rhizomes with a healthy stance becauseempirically many have used them as halitosis treatment in people with diabetes mellitus. The researchobjective was to formulate herbal mouthwash from extracts of natural ingredients, namely a combinationof ginger and lemongrass which has the potential as antibacterial causes of bad breath (halitosis) in peoplewith Diabetes Mellitus (DM). Material and Methods. The extraction of the sample will be carried out by amodified extraction method using ethanol and water solvents, then biological activity testing will be carriedout in-vitro with the diffusion method so that the antibacterial activity test against several bacteria that causehalitosis will be tested. Antibacterial sample is an active compound resulting from the extraction process.Bacteria that had been inoculated into the growth medium (NB) were put into sterile soft NA media (0.7%)with a concentration of 10,000.8,000,7,500 and 6,000 ppm, respectively. Results. There is an inhibitoryeffect, on p. gingivalis but the pattern of values is uncertain. A solution of formulation A with a concentrationof 75% occurs inhibition with an inhibition diameter of 15.7%. This inhibitory effect is not an activity offormulation A, because acetic acid also has the ability to inhibit bacteria. In the sample solution with aconcentration of 100% chitosan (w / v), the highest inhibition occurred with an inhibition diameter of 18.7mm / mg of the sample extract. Formulation A with a concentration of 25% (w / v), the lowest inhibitionoccurred. The test solution of formulation A with a concentration of 25% has shown an inhibitory effect onthe growth of Streptococcus mutans. This effect is stronger at concentrations of 100%, 75%, and 50%. Theantimicrobial effect actually increased with an increase in the concentration of the test solution in successionof 25%, 50%, 75%, 100%. Formulation C with a concentration of 10000ppm, 8000ppm, 7500ppm, 6000ppmshowed that the antimicrobial effect actually increased with an increase in the concentration of the testsolution in succession. This shows that there is a strong positive relationship between concentration andinhibition zone. Conclusion. All tests for both formulation A and formulation C using several concentrationsshowed quite good results with the antibacterial activity being directly proportional to the concentration, thegreater the concentration the greater the activity.